HAZARD AND RISK MAPPING OF TSUNAMI DISASTER USING HLOSS METHOD CASE STUDY: IDANO GAWO DISTRICT - Lubis, Lailatul Husna; Sahputra, Erry; Melati, Tia; Hanova, Yudha (Physics Study Programme, Faculty of Science and Technology UIN Syarif Hidayatullah Jakarta, 2025)
Idano Gawo District, Nias Regency has geographical characteristics that are vulnerable to tsunami. Based on the history of the earthquake in the Nias Islands in 2005, there was a release of megathrust earthquake energy caused by disturbance of the big Aceh earthquake on December 26, 2004. This earthquake was followed by a 2-3 meter high tsunami that hit several coastal areas in the Nias Islands, so disaster mitigation is needed. Mapping tsunami hazards and risks is an important effort for effective mitigation planning, by knowing the area of danger and tsunami risk based on a 16 meter height scenario. The method used in this study is the hloss and cost distance methods. Mapping the level of tsunami hazard and risk with a height of 16 meters using Arcgis Software. For processing tsunami disaster hazard and risk data using Microsoft Excel Software. Bozihona Village is an area that has a high level of danger with a total area of 3.76 km2 and a high level of tsunami risk with a total area of 3.77 km2.